2019
DOI: 10.1101/580092
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple genetic loci affect place learning and memory performance in Drosophila melanogaster

Abstract: Learning and memory are critical functions for all animals, giving individuals the ability to respond to changes in their environment. Within populations, individuals vary, however the mechanisms underlying this variation in performance are largely unknown. Thus, it remains to be determined what genetic factors cause an individual to have high learning ability and what factors determine how well an individual will remember what they have learned. To genetically dissect learning and memory performance, we used … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 118 publications
(173 reference statements)
1
2
0
Order By: Relevance
“…S5E), suggesting potential co-regulation of the coding and non-coding transcript in cis as previously reported for other lncRNAs-mRNA pairs (Engreitz et al, 2016). Drosophila wdp is a transmembrane protein with known functions in the wing disc (Takemura et al, 2020) and the trachea (Huff et al, 2002), and it has also been implicated in synaptic target recognition (Kurusu et al, 2008) and learning (Williams-Simon et al, 2019). While the sequence of the lncRNA LOC112590028 itself is not conserved, Drosophila has a lncRNA, CR44758 in the same position as LOC112590028, between wdp and Gp150 (Fig.…”
Section: Long Non-coding Rnas In Single-cell Sequencing Analysis Revealed By Iso-seqsupporting
confidence: 66%
“…S5E), suggesting potential co-regulation of the coding and non-coding transcript in cis as previously reported for other lncRNAs-mRNA pairs (Engreitz et al, 2016). Drosophila wdp is a transmembrane protein with known functions in the wing disc (Takemura et al, 2020) and the trachea (Huff et al, 2002), and it has also been implicated in synaptic target recognition (Kurusu et al, 2008) and learning (Williams-Simon et al, 2019). While the sequence of the lncRNA LOC112590028 itself is not conserved, Drosophila has a lncRNA, CR44758 in the same position as LOC112590028, between wdp and Gp150 (Fig.…”
Section: Long Non-coding Rnas In Single-cell Sequencing Analysis Revealed By Iso-seqsupporting
confidence: 66%
“…QTL Mapping and Heritability -We performed a genome scan on 741 RILs using a custom R script as described in Williams-Simon et al (2019). We used the average incapacitation times from each RIL as phenotype and applied the Haley-Knott regression (Haley and Knott 1992).…”
Section: A)mentioning
confidence: 99%
“…However, mapping approaches lack the resolution to identify single genes on their own (Mackay 2001). More recently researchers have been pairing mapping approaches with transcriptomics to identify candidate genes that influence complex traits (Cubillos et al 2017;Highfill et al 2017;Williams-Simon et al 2019;Wen et al 2019;Ng'oma et al 2020;Lecheta et al 2020), which was first introduced by Wayne and McIntyre (2002). While it is critically important to validate candidate genes that have been identified to be associated with complex traits, it has been a daunting task, and therefore few genetic studies of complex traits have definitively identified causal variants (Ding et al 2016;Highfill et al 2017;Gaspar et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila melanogaster is a model organism that has been extensively phenotyped and genotyped for a multitude of stress-resistance traits. These include but are not limited to: desiccation resistance, heat tolerance, resource acquisition, starvation resistance, and physiological changes Kennington et al 2001;Karan and Parkash 1998;Telonis-Scott et al 2016;Harbison et al 2005;Goenaga, Fanara, and Hasson 2013;Davidson 1990;King, Roff, and Fairbairn 2011;Williams-Simon et al 2019;Chippindale et al 1998;Burke et al 2010). Their widespread, historic use in genetic studies has made them a model organism for the elucidation of genetic mechanisms of quantitative traits (Roff and Mousseau 1987;Mackay et al 2012;Sokolowski 2001;Morgan 1910).…”
Section: Introductionmentioning
confidence: 99%
“…(Cridland et al 2013;Marriage et al 2014;Najarro et al 2015;Highfill et al 2016;Williams-Simon et al 2019;Singh et al 2022;Riddle and Farnoudi).…”
mentioning
confidence: 99%